Influence of Bracket and Composite Material in Conjunction with Saliva pH on Streptococcus mutans Adhesion: A Controlled In vitro Investigation - Leila Mohammadpour Belvirdy; Ahmad Sheibaninia; Shadab Safarzadeh Khosroshahi; Ali Valinejadi; Seyyed Khalil Shokouhi Mostafavi; Mohammad Javad Kharazi Fard (Biomedical and Biotechnology Research Journal)
Background: Streptococcus mutans adhesion to orthodontic appliances initiates biofilm formation and increases caries risk. This study evaluated how bracket material, composite type, and saliva pH jointly affect S. mutans attachment in vitro. Methods: Six bracket–composite combinations (plastic, metal, ceramic brackets × light-cure, self-cure composites) were tested under acidic (pH 5) and neutral (pH 7) artificial saliva. For each of the 12 subgroups, n = 6 samples were prepared. After pellicle formation, samples were incubated with *S. mutans (1.5 × 109 CFU/mL), and colony-forming units (CFUs) were counted. Data were analyzed using generalized estimating equations (GEEs) with α = 0.05. Results: At pH 5, mean CFU/mL for ceramic, metal, and plastic brackets were 87.77 ± 35.61, 59.10 ± 5.23, and 93.11 ± 83.25, respectively. Composite types yielded 72.18 ± 67.92 (light-cure) and 308.93 ± 75.19 (self-cure). GEE revealed no significant isolated effect of bracket material (P = 0.183) or composite type (P = 0.966), but a significant main effect of bracket material (P = 0.001) and bracket × composite interaction (P = 0.001) emerged when combined. At pH 7, bracket means were 816.38 ± 50.72, 393.32 ± 67.50, and 671.41 ± 83.25 CFU/mL for ceramic, metal, and plastic, respectively; light-cure and self-cure composites showed 84.33 ± 78.94 and 243.22 ± 67.43 CFU/mL. GEE indicated a nonsignificant bracket effect (P = 0.095), a significant composite effect (P = 0.001), and no interaction (P = 0.234). Conclusion: Saliva pH modulates material effects on S. mutans adhesion. Under acidic conditions, bracket–composite interactions drive adhesion differences, whereas at neutral pH, composite type predominates. Appliance selection should consider both material pairing and oral pH environment.